From PMO to VMO : managing for value delivery - Augustine, Sanjiv; Cuellar, Roland; Scheere, Audrey (Berrett-Koehler Publishers, Inc., 2021)
"When so many enterprises have the strategic goal of maximizing product value to customers, changing their project management office (PMO) into a value management office (VMO) will help them do it"--